Microanatomy of Thalamic Radiations - kakou, Medard; Kouakou, Fulbert; N’dri Oka, Dominique; Slim Mbende, Alban; Peltier, Johann; Velut, Stéphane (International Journal of Human Anatomy, 2017)
Background Thalamic radiations also known as thalamocortical pathways are reciprocal myelinated nerve fibers, arranged in a fanning pattern, grouped into tracts or fasciculi; and connecting the thalamus to the cerebral cortex. Detailed in vitro study of these tracts is seldom reported in the literature. Objective We sought to describe the microanatomy of thalamic radiations by means of the fiber-dissection technique to discuss challenges in dissection techniques and anatomic nomenclature, and follow through with a literature review. Methods Twenty formalin-fixed normal human hemispheres were dissected according to Klingler’s fiber-dissection technique under operative microscope. Results Thalamic radiations are reciprocal myelinated nerve fibers connecting the thalamus to the cerebral cortex and are referred to as corticothalamic and thalamocortical tracts. They are the most medial fibers of the internal capsule and consist of anterior (thalamofrontal), superior (thalamo-fronto-parietal or thalamoparietal), posterior (thalamooccipital) and inferior (thalamotemporal) thalamic fasciculi. Conclusion From the cerebral cortex, thalamic radiation fibers fan out into the thalamus and are the most medial fibers of the internal capsule. There is a great deal of controversy surrounding the distinction between anterior and superior thalamic radiations, sub-ependymal stratum and the fronto-occipital fasciculus.
Keywords: Thalamic radiations; brain white matter; Klingler; dissection.